(untitled) (College of Basic Education Research Journal, 2025)
Two simple, rapid, highly sensitive, and accurate spectrophotometric methods were utilized to estimate catecholamine drugs methyldopa and isoprenaline. Oxidative coupling reaction was used to estimate methyldopa using ferric nitrate as an oxidizing agent and coupled with mesalazine reagent in an alkaline medium of sodium hydroxide solution producing a blue color measured at λ max 578 nm, linearity of calibration curve was in concentration range 2 -28 µg/ml with a correlation coefficient of 0.9986, molar absorptivity and Sandell’s index were calculated , equal to 0.566×104 l.mol-1.cm-1 and 0.042 µg.cm-2 respectively, limit of detection and quantification values were equal to 0.06509 and 0.2169 µg/ml, respectively. Isoprenaline was estimated using a azo-coupling reaction using a diazotized p-Nitroaniline reagent coupled with isoprenaline in an alkaline medium of sodium hydroxide solution and 5rt presence of TritonX-100(1%) surfactant solution. The orange-red azo dye produced which measured at λ max 510 nm., calibration curve linearity was in concentration range between 2 -20 µg/ml with a correlation coefficient of 0.9985, molar absorptivity , Sandell’s index were calculated and equal to 2.3434×104 l.mol-1.cm-1 and 0.0105 µg.cm-2 respectively, LOD and LOQ were equal to 0.02119 and 0.07064 µg/ml, respectively. These methods proved successful in estimating methyldopa and isoprenaline in pure forms and pharmaceutical preparations.